Nya välfärdsprofessioner i offentlig förvaltning: En studie av rollen som kommunal digitaliseringsstrateg - Werkström,Johan (2024)
Local governments are today facing an increasingly complex reality marked by financial restraints, new demands from citizens and a growing competition with the private sector in providing welfare services. This complexity has led local governments to seek new types of competence, knowledge and skills among employees. Consequently, new roles have emerged within local government, with the strategist being a prominent example. Prior research has shown that this position is filled with uncertainty and often met by skepticism from the surrounding organization. The aim of this thesis is to enhance our understanding of new professions in the welfare sector, with the digital strategist in local government as an empirical case. A framework combining prior theoritizations of new professions with institutional logics is employed to deepen our understanding of the development as well as of tensions associated with the role. The analyzed material consists of job advertisements and explorative interviews with current practitioners. The main findings reveal that the role largely aligns with the characteristics of a new type of profession, but is often far from a natural element in the organization. This tension can to large extent be attributed to conflicting institutional logics, which the strategists learn to navigate to some extent but which also hinders their professional practice.
Keywords: Welfare Professions; Strategists; Local Government; Digitalization; Institutional Logics